Importance of livestock in small-scale farming systems of rural coffee areas in Colombia - J MORA-DELGADO; V A HOLGUÍN (Indian Journal of Animal Sciences, 2014)
Rationally oriented livestock systems play a positive role in rural livelihoods. In this study, surveys and interviews were carried out in 49 coffee growers from Andean region of Colombia, where domestic animals were used as source of protein food, nutrient recycling, a way to increase income and a source of commercial products. The farmers were classified in C3, C2 and C1 clusters, according to socioeconomics and technological indicators extracted from the survey. Different features of farming system were identified in each cluster, among them C1 has the largest farm area (average 32.2±20.2 ha). The clusters C1, C2 and C3 have an average of 17.6±8.6, 8±4.8 and 4±2.5 cows / farm respectively. In addition, coffee growers have other livestock species like chickens, hens and pigs, that are oriented mainly to own consumption. In conclusion, livestock systems, particularly small scale cattle production contribute to the livelihoods and wellbeing of coffee growers in the Andean area of Colombia.